Diccionario para profesionales de la traducción : terminología básica que todo traductor debe aprender - Luna, Rosa; Monteagudo Medina, Mary Ann (Universidad Peruana de Ciencias Aplicadas, 2017)
The main objective of this dictionary is to systematize the terminology employed in the Hispanic translation market. The publication is aimed at students and faculty in translation programs, professional translators and translation users, who will find more than 1000 terms in connection with the current market's behavior. The terms are listed and divided by fields, properly coded contexts with source, references and notes.